As recepções da Quasar Cia. de Dança: influências e interpretações sobre o espetáculo No Singular (2012) - Mazza, Samuel Nogueira (2020)
This study aims to analyze the art scene, more specifically the dance scence, in the city of Goiânia from the 2000s. The main object of analysis is No Singular (2012), a performance by Quasar Cia. De Dança, a dance company established in the 1990s and kept active at least until the second half of the 2000s. This work’s intention is to understand and discuss interpretations about the company developed by academia, the media and art critics. The research questions values commonly attributed to the company’s work, such as contemporary dance, innovation, singularity and isolation. Such values, or ideas, are usually linked to Quasar’s choreographer Henrique Rodovalho, who rises as a central figure in Goiás State cultural scene, following the recognition of the dance company in the 1990s. In this context, the study’s goal is to discuss these ideas from a broader perspective about cultural production, establishing a dialogue with what has been released in academic papers and newspaper articles about art and culture in the city of Goiânia.